(untitled) - Itagaki, Hiroshi (London, 1997)
This book examines the application of key elements of the Japanese Production System to five East Asian countries whose social and managerial environments differ from each other as well as from those of Japan. To analyse the key elements, a working model was constructed and applied. Using this model, these Japanese plants are also compared with those in the US where a previous study was undertaken. It includes contributions from leading researchers and academics.
Keywords: Quản lý sản xuất,Production management; Nhật Bản,Japan